2020
DOI: 10.2147/rmhp.s264037
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychological Distress Amongst Health Workers and the General Public During the COVID-19 Pandemic in Saudi Arabia</p>

Abstract: Background The rapid spread of COVID-19 worldwide has confined millions of people to their homes and has caused a substantial degree of psychological distress. This study aims to investigate the psychological distress impact of the COVID-19 pandemic among the Saudi population. Methods This is a cross-sectional study, using data collected from 3036 participants via an online self-reported questionnaire. The psychological distress was constructed using the COVID-19 Peritr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
145
9
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(197 citation statements)
references
References 28 publications
35
145
9
8
Order By: Relevance
“…Equally, the results revealed that the respondents' level of anxiety was significantly different based on their gender and educational levels. These results support the findings reported by Al-Hanawi et al [22] that respondents' level of worry or concern attributed to COVID-19 differs significantly across gender and educational level. This result is also in line with previous studies [23,24] carried out in China, indicating that females have higher levels of anxiety compared to males.…”
Section: Discussionsupporting
confidence: 91%
“…Equally, the results revealed that the respondents' level of anxiety was significantly different based on their gender and educational levels. These results support the findings reported by Al-Hanawi et al [22] that respondents' level of worry or concern attributed to COVID-19 differs significantly across gender and educational level. This result is also in line with previous studies [23,24] carried out in China, indicating that females have higher levels of anxiety compared to males.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the results revealed that the respondents' level of anxiety was signi cantly different based on their gender and educational levels. These results support results reported by Al-Hanawi et al [22] that respondents' level of worry due to COVID-19 differs signi cantly across gender and educational level. The result also in line with a previous studies [23,24] in China, which indicated that females have high levels of anxiety compared to males.…”
Section: Discussionsupporting
confidence: 91%
“…Equally, the results revealed that the respondents' level of anxiety was signi cantly different based on their gender and educational levels. These results support the ndings reported by Al-Hanawi et al [22] that respondents' level of worry or concern attributed to COVID-19 differs signi cantly across gender and educational level. This result is also in line with previous studies [23,24] carried out in China, indicating that females have higher levels of anxiety compared to males.…”
Section: Discussionsupporting
confidence: 91%